Comparative efficacy of eDNA and conventional methods for monitoring wetland anuran communities - Wikston, Madison; Breton, Brie-Anne A.; Vilaça, Sibelle Torres; Bennett, Amanda M.; Kyle, Christopher J.; Beresford, David V.; Lesbarrères, David; Wilson, Chris C.; Green, David M.; Fortin, Marie-Josée; Murray, Dennis L. (Frontiers in Ecology and Evolution, 2023)
Documenting biodiversity, species occurrence, and species status requires reliable monitoring techniques, but the complex life history and cryptic behaviour of many anurans create challenges for conventional monitoring approaches. Environmental DNA (eDNA) surveys are a promising alternative (or complement) to conventional anuran monitoring, but their relative success has not been fully tested. We assessed the comparative efficacy of targeted eDNA detection via qPCR and three conventional amphibian survey methods (visual encounter, breeding call, and larval dipnet surveys) for detecting nine anuran species in natural wetlands in southern Ontario, Canada. Our analyses revealed that all assessment methods yielded imperfect detection, with visual encounter and eDNA surveys detecting the greatest species richness and eDNA surveys requiring the fewest sampling events. Amphibian community composition results differed among survey methods and sampling events, and detection efficacy was markedly variable, with some species requiring 2-3 methods to maximize detection success. Notably, two relatively terrestrial species (Anaxyrus americanus and Hyla versicolor) had relatively low and seasonally-variable eDNA detection rates, suggesting that species-specific ecology likely affects eDNA presence or detection. These findings suggest that optimized monitoring for complex anuran communities may require application of multiple monitoring methods, which may need to be tailored to individual target species or communities.